Early-stage differentiation between Alzheimer’s disease and frontotemporal lobe degeneration: Clinical, neuropsychology, and neuroimaging features - Li, Pan; Quan, Wei; Wang, Zengguang; Liu, Ying; Cai, Hao; Chen, Yuan; Wang, Yan; Zhang, Miao; Tian, Zhiyan; Zhang, Huihong; Zhou, Yuying (Frontiers in Aging Neuroscience, 2022)
Background : Alzheimer’s disease (AD) and Frontotemporal lobar degeneration (FTLD) are the two most frequent neurodegenerative dementia, despite existing diagnostic criteria, achieving early diagnosis is still challenging. Here we aimed to make the differential diagnosis of AD and FTLD from clinical, neuropsychology and neuroimaging features. Methods: In this retrospective study, we selected 95 patients with PET-CT defined AD and 106 patients with PET-CT/biomarker-defined FTLD. We performed structured chart examination to collect clinical data and ascertain clinical features. A series of neuropsychological scales were used to assess the neuropsychological characteristics of patients. Automatic tissue segmentation of brain by Dr. Brain tool was used to collect multi-parameter volumetric measurements from different brain areas. All patients’ structural neuroimage data were analysis and to obtain brain structure and white matter hyperintensities (WMH) quantitative data. Results: The prevalence of vascular disease associated factors were higher in AD patients than that in FTLD group. 56.84% of patients with AD carried at least one APOE ε4 allele, which is much high than that in FTLD patients. First symptoms were more often cognitive impairment than behavioral abnormality in patients with AD. On the contrary, behavioral abnormalities are prominent early manifestations of FTLD, and few patients may be accompanied by memory impairment and motor symptoms. In direct comparison, patients with AD had slightly more posterior lesions and less frontal atrophy, whereas patients with FTLD had more frontotemporal atrophy and less posterior lesions. The WMH burden of AD was a significant higher, especially in cortical areas, while the WMH burden of FTLD was higher in periventricular areas. Conclusions: These results indicate that dynamic evaluation of cognitive function, behavioral and psychological symptoms and multimodal neuroimaging are helpful for the early diagnosis and differentiation between AD and FTLD.